Historic and recent progress in solar chimney power plant enhancing technologies - Al-Kayiem, H.H. (Elsevier Ltd, 2016)
Upon the basic idea of the updraft solar heating, the solar chimney was proposed and implemented as a model and a prototype by many research and industrial bodies. Although the system efficiency is below 2, but it is a promising technology to harness and convert the solar energy to electric power through three basic components; namely: solar collector, tower or chimney, and wind turbine-generator unit. The low efficiency, the bulk size and the high dependency on the solar irradiation are the major issues experienced in the solar chimney power plants. Since the implementation of the first prototype in Manzenares, numerous attempts have been reported to enhance the performance of the system. The present paper is compiling most of the reported attempts to enhance the performance of the solar chimney power plant. The conclusion drawn is that the system performance can be enhanced considerably via integration with another source of thermal energy, or by using efficient solar thermal energy storages. This paper provides a platform to the researchers in the field to understand and get detailed literature on the enhancing technologies of the solar chimney power plant current updates. Â© 2016 Elsevier Ltd. All rights reserved.